Estudo da influência da temperatura de queima da casca de arroz no desempenho da argamassa de revestimento - Olivo, Paola (2020)
ABSTRACT The use of industrial by-products has been shown to be advantageous when incorporated in mortars and concrete. Its use, besides reducing cement consumption, increases the mechanical resistance and durability of the structures. The rice husk (RH) comes from the agribusiness and its calcination generates the rice husk ash (RHA), a material rich in SiO2. However, this material has great variability in its chemical composition and does not qualify for commercialization as active silica.Currently, it is possible to find works available on the use of RHA as a partial replacement of cement and even as an addition, acting as a pozzolan. When the rice husk is processed, controlling the calcination temperature, it may present a greater or lesser tendency to crystallinity. The present work aims to study the influence of the calcination temperature of the rice husk through XRD, where the calcination temperatures were chosen based on the amorphous character of the material. The performance of mixed coating mortar was analyzed, evaluating the pozzolanicity, the performance in the fresh state and the hardened and solid state of the microstructure. The choice of calcined materials (RHA’s) were temperatures of 300, 400 and 500ºC. The results obtained showed the influence of the RH temperature control for the study carried out in the fresh state and in the analysis of the microstructure, while the pozzolanicity and hardened state tests showed their similar properties.